The instrumental rule - Fix, JD (Cambridge University Press, 2020)
Properly understood, the instrumental rule says to take means that actually suffice for my end, not, as is nearly universally assumed, to intend means that I believe are necessary for my end. This alternative explains everything the standard interpretation can—and more, including grounding certain correctness conditions for exercises of our will unexplained by the standard interpretation.